House with Repulped Paper-Walled That Has Heat Energy Efficient - Noerwasito, Vincentius Totok (RUAS, 2012)
This paper describes research regarding the relationship between wall material, heat energy, and floor area of simple house building with repulped paper-walled. Heat energy is energy utilized to reduce heat into the building. Goals of this research found design building types that have optimum to heat energy and floor area. This research used type of houses for low income as samples. Variables house is house type 21, 36, 45, 54 and 70. Methodology utilized the simulation and optimation. Result research showed that type 54 is simple house that owning heat energy efficient.Keywords: house, repulped paper, ratio, heat, efficient